Peran Kepala Sekolah Sebagai Pemimpin Dalam Pendidikan Di Sekolah SMP IT Bina Insan - Suyono Suyono; Hajar Marhani; Ajeng Sri Hamidiat; Auliya Amanda (Jurnal Dirosah Islamiyah, 2023)
Leadership is defined as the art or process of influencing and directing other people, so that they want to try to achieve the goals to be achieved by the group. Islamic education leadership is a leader as a responsible individual in an Islamic religious education institution, has an obligation to try so that all the potential that exists in the institution can be utilized as well as possible in order to achieve the expected goals. Descriptive research methodology through a qualitative approach, namely the technique of data collection is done through interviews, observation, and documentation. After that the data collected was analyzed using qualitative descriptive techniques, and finally drawing conclusions. Based on the results of the research conducted, namely that in leading it is necessary to be wise, able to accommodate and able to accommodate complaints from all teachers. After all, a leader is an example and role model. Not only governing but must be able to provide service. Because the problems that arise from the teacher will later affect their performance. Keywords: leadership, education, and principals